EFFECT OF ORGANIC SOURCES OF NUTRIENTS ON POTATO PRODUCTION IN WEST BANGAL - Chettri, M; Basu, A; Konar, A; Mondal, A. B. (Potato Journal, 2013)
A field experiment was conducted during winter season of 2003-04 and 2004-05 at Hooghly district of West Bengal to study the effect of organic sources of nutrients on potato production as compared to inorganic sources of nutrients. Maximum tuber yield of potato was recorded with the application of inorganic sources of nutrients (NPK). Though the lower tuber yield was produced by the organic sources of nutrients (FYM) but it was economically profitable than the potato produced through inorganic sources of nutrients.